2022
DOI: 10.1007/s00018-022-04583-w
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasites utilize two essential plasma membrane fusogens for gamete fertilization

Abstract: Cell fusion of female and male gametes is the climax of sexual reproduction. In many organisms, the Hapless 2 (HAP2) family of proteins play a critical role in gamete fusion. We find that Plasmodium falciparum , the causative agent of human malaria, expresses two HAP2 proteins: Pf HAP2 and Pf HAP2p. These proteins are present in stage V gametocytes and localize throughout the flagellum of male gametes. Gene deletion analysis and genetic cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Additionally, the fact that other eukaryotic fusogens (e.g., EFF-1, AFF-1, and GCS1) were shown to be less efficient in vitro than their viral counterparts ( Avinoam et al, 2011 ; Valansi et al, 2017 ; Kumar et al, 2022 ) may explain why previous studies failed to detect fusion of somatic cells expressing IZUMO1 and JUNO ( Bianchi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the fact that other eukaryotic fusogens (e.g., EFF-1, AFF-1, and GCS1) were shown to be less efficient in vitro than their viral counterparts ( Avinoam et al, 2011 ; Valansi et al, 2017 ; Kumar et al, 2022 ) may explain why previous studies failed to detect fusion of somatic cells expressing IZUMO1 and JUNO ( Bianchi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…GCS1 is also essential to fuse gametes in the malaria parasite Plasmodium , in the slime mold Dictyostelium , and in the algae Chlamydomonas ( Liu et al, 2008 ; Hirai et al, 2008 ; Okamoto et al, 2016 ). It was subsequently demonstrated that the expression of A. thaliana and Plasmodium falciparum GCS1 is sufficient to fuse mammalian cells in culture ( Valansi et al, 2017 ; Kumar et al, 2022 ); thereby GCS1 is a bona fide fusogen. GCS1 structure is similar to class II viral glycoproteins (e.g., rubella and zika viruses; Fédry et al, 2017 ; Pinello et al, 2017 ; Valansi et al, 2017 ; Feng et al, 2022 ) and fusion family (FF) proteins from nematodes and other organisms ( Mohler et al, 2002 ; Sapir et al, 2007 ; Pérez-Vargas et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In P. falciparum, HAP2 is expressed throughout the plasma membrane of male gametocytes beginning at stage II of development, and in fully differentiated microgametes. Its paralog, HAP2p, shows a patchier membrane expression pattern, and begins to be expressed later during gametocyte development, and interestingly on stage V female gametocytes 50 . Whether HAP2p functions bilaterally to promote gamete fusion in P. falciparum, as described here for HAP2-2 in L. tropica, has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Pf s47 plays an important role in protecting ookinetes from mosquito’s immune system, Pf s47 could be a potential TBV candidate ( 93 ). The Hapless 2 (HAP2) family of proteins play a critical role in gamete fusion, and immunization with protein fragments of Pf HAP2, Pf HAP2p and Pb HAP2 generated transmission-blocking activity ( 150 , 151 ). Recombinant Pb HAP2 protein administered in rabbits showed high immunogenicity by inducing HAP2-specific antibodies which inhibited in vitro ookinete formation and oocyst formation in Anopheles midgut ( 151 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%